An empirical investigation of market risk, dependence structure, and portfolio management between green bonds and international financial markets. (10th September 2022) - Ejaz, Rimsha; Ashraf, Sumaira; Hassan, Arshad; Gupta, Ankit
Abstract: The study aims to explore the market risk, dependence structure, and portfolio diversification benefits of green bonds with Islamic and conventional (equity, bonds, and energy) markets. We first examine the market risk dynamics and dependence structure between green bonds and the international financial markets by using value-at-risk (VaR), copula models, and the Copula-VaR approach over the period from July 2014 to August 2020. Findings reveal the existence of the symmetric upper (lower) tail dependence between green bonds and international financial markets, except for the conventional bonds market with zero dependence. Our empirical results suggest that international financial markets possess different risk profiles, and the investors should not treat them as homogenous assets to combine with green bonds. Moreover, we also explore the portfolio diversification benefits, using hedge ratios, optimal portfolio weights, and hedging effectiveness for all pairs of green bonds-international financial markets. The results suggest that Islamic bonds and the oil markets are best to hedge green bonds, followed by conventional bonds, conventional equity, and the Islamic equity market. These results provide implications for effective risk management and fund allocation to policymakers and socially responsible investors. The study's findings are critical for current and future investors for efficient capital allocation in the environmental and ethically responsible assets.